Acceptability of using a nasogastric refeeding protocol with adult patients with medically unstable eating disorders. Issue 1 (14th June 2022) - Matthews‐Rensch, Kylie; Young, Adrienne; Cutmore, Clare; Davis, Amanda; Jeffrey, Shane; Patterson, Susan
Abstract: Rationale, Aims and Objectives: Nasogastric feeding is becoming commonly used to support patients with medically compromised eating disorders. Previous research has demonstrated the safety of this approach, however there is limited evidence as to how adult patients and staff perceive this feeding method. This study aimed to describe the acceptability of a nasogastric refeeding protocol with adult patients with medically unstable eating disorders and the staff involved in their treatment. Method: This was a qualitative exploratory study using semi‐structured interviews conducted in acute medical wards of a tertiary hospital where nasogastric nutrition is the sole source of nutrition for the first 7 days of the eating disorder admission. Data were analysed using the Framework method. Results: Eight patients (100% female, median: 22 years old, n  = 6 diagnosed with anorexia nervosa) and 12 staff members (medical n  = 5, nursing n  = 5, dietitians n  = 2; median: 8.5 years clinical experience) were interviewed. Patients reported that nasogastric feeding was tolerable, however concerns were raised regarding communication and the desire for concurrent oral feeding. Acceptability from staff was influenced by perceived competence, confidence, tensions around patient‐centred care,  and working with stigma and ambivalence. Conclusions: Consideration needs to be given as to whether a 'nil by mouth' status during nasogastric feeding further impacts recommencing an oral diet to progress treatment. Improvements are required within the current service, including improved communication, additional educational resources for patients,  and allowing patients to partake in decision‐making as able.